1975
DOI: 10.1152/ajplegacy.1975.229.1.240
|View full text |Cite
|
Sign up to set email alerts
|

Microelectrophoresis of PGE1 onto single units in the rabbit hypothalamus

Abstract: Prostaglandin E1 (PGE1) when micro-injected into the preoptic anterior hypothalamus (PO/AH) of conscious rabbits is a potent pyrogenic agent. We have investigated the action of PGE1 on the activity of single units of the PO/AH area using the microelectrophoretic technique. One hundred and thirty-eight PO/AH units were tested both for their response to changes in local PO/AH temperature and for their response to PGE1 application. Less than 9.0% of the total population of units tested showed any response to PGE1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1

Year Published

1977
1977
1992
1992

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 0 publications
2
10
1
Order By: Relevance
“…The present results on POA neurones are somewhat different from these previous ones, in which predominantly facilitatory responses of POA neurones in vitro (Watanabe et al 1987) or the low sensitivity to PGE2 in POA neurones in vivo (Stitt et al 1975) were demonstrated. However, the application of PGE2 in unphysiologically high concentrations (e.g.…”
Section: Responsiveness Of Ovlt and Poa Neurones To Pge2contrasting
confidence: 99%
See 2 more Smart Citations
“…The present results on POA neurones are somewhat different from these previous ones, in which predominantly facilitatory responses of POA neurones in vitro (Watanabe et al 1987) or the low sensitivity to PGE2 in POA neurones in vivo (Stitt et al 1975) were demonstrated. However, the application of PGE2 in unphysiologically high concentrations (e.g.…”
Section: Responsiveness Of Ovlt and Poa Neurones To Pge2contrasting
confidence: 99%
“…Since it has been proposed that warm-sensitive and cold-sensitive neurones facilitate heat defence responses and cold defence responses of thermoregulation, respectively (Boulant, Curras & Dean, 1989;Hori, 1991), these changes in POA thermosensitive neurones are appropriate in explaining the changes in thermoregulatory responses during the rising phase of fever, i.e., inhibition of heat defence responses and facilitation of cold defence responses. However, no studies on the direct application of PGE2 on POA neurones have revealed a consistent relationship between the responsiveness of POA neurones to PGE2 and temperature (Stitt et al 1975: Boulant & Scott, 1986Watanabe et al 1987;Morimoto et al 1988). In confirmation with these findings, no correlation between the responsiveness of POA neurone to PGE2 and temperature was found in the present study which was undertaken in a more carefully controlled experimental condition than in the previous ones.…”
Section: Responsiveness Of Ovlt and Poa Neurones To Pge2supporting
confidence: 75%
See 1 more Smart Citation
“…Antagonism of the NA response of cerebellar Purkinje neurons by PGE has been reported (SIGGINS et al, 1971), but no such effect has been observed on hypothalamic neurons (STIT and HARDY, 1975;JELL and SWEATMAN, 1977). The present experiments revealed modulation by PGD2 of both the NA response and the ACh responses of LPOA neurons.…”
Section: Discussionsupporting
confidence: 44%
“…Direct effects on neuronal activity in the hypothalamus were mainly excitatory and the incidence of responsive neurons ranged from 9 to 83% (JELL and SWEATMAN, 1977;POULAIN and CARETTE, 1974;STIT and HARDY, 1975). In contrast, the effects of PGD2 on the CNS have received less attention.…”
Section: Discussionmentioning
confidence: 99%